Home in the Poetry of Saudi Arabia Poets: Abdus-Salam Hafeth an Example of a Distinguished Arab (2) - Yahya Saleh Hasan Dahami (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This study aims to shed light on some literary aspects of modern Saudi Arabic poetry, focusing on the concept of homeland as an example of the standing of modern Saudi poetry, with a specific reference to a contemporary Saudi poet, Abdus-Salam Hashem Hafeth. The researcher seeks to show the poet's intellect by showing his gorgeous metropolis as a symbol of his love for the grand home - the Kingdom of Saudi Arabia. The study begins with a brief introduction to Arabic poetry and its language. Then it gives a symbolic picture of the outstanding Saudi poet – Abdus-Salam Hashem Hafeth and Saudi poetry in general. Following that, the study takes a critical-analytical approach to the second four verse lines of Hafeth's poem, 'Nostalgia, Oh my Home,' focusing on the concept of home as its main theme as well talent of the poet in using the grand Arabic language. Eventually, the research is concluded with a short premise and comments.